Quartz Crystal Resonator Parameter Calculation Based on Impedance Analyser Measurement Using GRG Nonlinear Solver - Setyawan Purnomo Sakti (Fakultas MIPA Universitas Brawijaya, 2014)
Quartz crystal resonator which is used as a basis for quartz crystal microbalance (QCM) sensor was modelled using many different approach. The well-known model was a four parameter model by modelling the resonator as a circuit composed from two capacitors, inductor and resistor. Those four parameters control the impedance and phase again frequency applied to the resonator. Electronically, one can measure the resonator complex impedance again frequency by using an impedance analyser. The resulting data were a set of frequency, real part, imaginary part, impedance value and phase of the resonator at a given frequency. Determination of the four parameters which represent the resonator model is trivial for QCM sensor analysis and application. Based on the model, the parameter value can be approximately calculated by knowing the series and parallel resonance. The values can be calculated by using a least mean square error of the impedance value between model and measured impedance. This work presents an approach to calculate the four parameters basic models. The results show that the parameter value can be calculated using an iterative procedure using a nonlinear optimization method. The iteration was done by keeping two independence parameters R0 and C0 as a constant value complementary. The nonlinear optimization was targeted to get a minimum difference between the calculated impedance and measured impedance.Keywords— QCM Sensor, four parameter model, impedance measurement.